Longitudinal Changes in Peripapillary Retinal Nerve Fiber Layer and Macular Ganglion Cell Inner Plexiform Layer in Progressive Myopia and Glaucoma Among Adolescents - Xiao, Hui; Zhong, Yimin; Ling, Yunlan; Xu, Xiaoyu; Liu, Xing (Frontiers in Medicine, 2022)
Purpose: This study aimed to investigate the differences in longitudinal changes in the peripapillary retinal nerve fiber layer (pRNFL) and macular ganglion cell plus inner plexiform layer (GCIPL) caused by progressive myopia and glaucoma among adolescents. Design: This was a retrospective observational study. Methods: Forty-seven and 25 eyes of 47 and 25 adolescents with myopia progression(MP) and glaucoma progression(GP), respectively, who were followed up at the Zhongshan Ophthalmic Center for at least 3 years were included in the study. The pRNFL and GCIPL measured at the initial and last visits were analyzed. Results: The median follow-up period was both 5 years for the two groups. During follow-up, the whole, superior, and inferior pRNFL decreased in both the MP and GP groups, (P<0.001). Nasal pRNFL decreased in the MP group (P<0.001) but had no significant difference in the GP group (P=0.19). Temporal pRNFL was increased in the MP group (P<0.001) but decreased in the GP group (P<0.001). The average and sectoral GCIPL decreased in both groups (P<0.001). The annual change rate of temporal pRNFL and pRNFL at 10, 8, 9, and 7 clock-hour sectors and the inferotemporal GCIPL has better diagnostic value to differentiate glaucoma from myopia(the area under the receiver operating characteristic curve, AUC＞0.85). Conclusion: Glaucoma and myopia progression could cause loss of the pRNFL and GCIPL in adolescents; however, the loss patterns were different between the two groups. The temporal quadrant and 7, 8, 9, 10 clock-hour sector pRNFL and the inferotemporal GCIPL can help distinguish pRNFL and GCIPL loss caused by glaucoma or myopia progression.